1998
DOI: 10.1148/radiology.206.1.9423651
|View full text |Cite
|
Sign up to set email alerts
|

Annular tears and disk herniation: prevalence and contrast enhancement on MR images in the absence of low back pain or sciatica.

Abstract: Annular tears and focal disk protrusions on MR images, with or without contrast enhancement, are frequently found in an asymptomatic population. Extruded disk herniation, displacement of nerve root, and interruption of annuloligamentous complex are unusual findings in an asymptomatic population and can be more closely related to patients with LBP or sciatica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
4
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(101 citation statements)
references
References 0 publications
2
91
4
3
Order By: Relevance
“…(Table 3) Pathria et al 36 developed a grading system based on degenerative facet changes identified in oblique radiographs and CT. Weishaupt et al 37 correlated changes in CT with those found in MRI, using the parameters of facet joint space, articular hypertrophy, and the presence of osteophytes to define their grades. Using MRI, Stadnik et al 38 identified degenerative changes, describing the concept as High Intensity Zones (HIZ), positively correlated with disc rupture.…”
Section: Resultsmentioning
confidence: 99%
“…(Table 3) Pathria et al 36 developed a grading system based on degenerative facet changes identified in oblique radiographs and CT. Weishaupt et al 37 correlated changes in CT with those found in MRI, using the parameters of facet joint space, articular hypertrophy, and the presence of osteophytes to define their grades. Using MRI, Stadnik et al 38 identified degenerative changes, describing the concept as High Intensity Zones (HIZ), positively correlated with disc rupture.…”
Section: Resultsmentioning
confidence: 99%
“…Многочисленные исследования, между тем, де-монстрируют, что определяемые гистологически и на МРТ разрывы фиброзного кольца дисков у пациентов с БНС не могут рассматриваться как надежный маркер формирования болевых проявлений. Было неоднократно показано, что изолированный дефект фиброзного кольца далеко не всегда сопровождается БНС [11,12]. Между тем этот фактор может играть важную роль в процессе форми-рования дегенеративного каскада.…”
Section: воспалительные механизмы дискогенной боли в спинеunclassified
“…Снижение активности воспалительных медиаторов при грубой дегенерации МПД может быть связано со сниже-нием числа клеток МПД и их метаболической активно-сти. Важно, что этот паттерн сочетания высокой экспрес-сии воспалительных медиаторов с умеренными дегенера-тивными изменениями МПД соотносится с наиболее вы- 12,2015 ОБЗОРЫ сокой частотой манифестации БНС. Известно, что у па-циентов с наличием вышеописанного паттерна после ра-диочастотой аблации симптомы БНС регрессируют при отсутствии изменений на МРТ.…”
Section: воспалительные механизмы дискогенной боли в спинеunclassified
“…25,26,67 A wide variety of spinal pathology, including disk protrusions, herniations, free fragments, and annular tears have been demonstrated on the MRIs of asymptomatic persons. 37,45,50,81,93,96 The radiologist will often suggest clinical correlation of imaged pathology on the official report. The comprehensive clinical examination will typically provide the appropriate relevance to any pathology identified with an imaging study.…”
Section: The Relevance Of Pathology Revealed In Diagnostic Imagesmentioning
confidence: 99%
“…Careful clinical correlation is required for any imaged pathology, as anatomic abnormalities of the lumbar spine, including degenerative changes and abnormal discs, are commonly found in the asymptomatic population and these findings increase in frequency with older patients. 50,96 The screening strategy is dependent upon the sensitivity of the ESR for infectious processes, as plain films have the least sensitivity for spinal infections. Radiographic abnormalities may not appear in spinal radiographs for 2 to 8 weeks.…”
Section: Imaging Studies For Lbpmentioning
confidence: 99%